The cardiac phenotype induced by PPARα overexpression mimics that caused by diabetes mellitus - Finck, Brian N. (American Society for Clinical Investigation, 2002)
Recent evidence has defined an important role for PPARα in the transcriptional control of cardiac energy metabolism. To investigate the role of PPARα in the genesis of the metabolic and functional derangements of diabetic cardiomyopathy, mice with cardiac-restricted overexpression of PPARα (MHC-PPAR) were produced and characterized. The expression of PPARα target genes involved in cardiac fatty acid uptake and oxidation pathways was increased in MHC-PPAR mice. Surprisingly, the expression of genes involved in glucose transport and utilization was reciprocally repressed in MHC-PPAR hearts. Consistent with the gene expression profile, myocardial fatty acid oxidation rates were increased and glucose uptake and oxidation decreased in MHC-PPAR mice, a metabolic phenotype strikingly similar to that of the diabetic heart. MHC-PPAR hearts exhibited signatures of diabetic cardiomyopathy including ventricular hypertrophy, activation of gene markers of pathologic hypertrophic growth, and transgene expression–dependent alteration in systolic ventricular dysfunction. These results demonstrate that (a) PPARα is a critical regulator of myocardial fatty acid uptake and utilization, (b) activation of cardiac PPARα regulatory pathways results in a reciprocal repression of glucose uptake and utilization pathways, and (c) derangements in myocardial energy metabolism typical of the diabetic heart can become maladaptive, leading to cardiomyopathy.